Pharmacological Properties of Propiverine Contribute to Improving Lower Urinary Tract Dysfunctions in Rats with Spinal Cord Injuries - Sakakibara, F.; Takahama, K.; Nanri, M.; Sasaki, E. (Drug Research, 2016)
Patients with spinal cord injury (SCI) usually develop lower urinary tract dysfunctions, including detrusor overactivity which is also known to be a risk factor for upper urinary tract dysfunction. Antimuscarinic agents, such as propiverine, have been used clinically for the treatment of detrusor overactivity. Also, propiverine has been known to possess antagonistic activity against L-type Ca2+ channels and transient receptor potential vanilloid subtype 1 (TRPV1), in addition to activity against muscarinic receptors. These mechanisms of action may contribute to improving detrusor overactivity in SCI. We therefore investigated the effects of antagonists of these mechanisms on non-voiding contraction (NVC) in SCI rats that are similar to clinical cases of detrusor overactivity, and considered whether these action mechanisms contribute to the incidence of NVC in SCI. Cystometry was performed in rats 4 weeks after spinal transection. Urinary functions were evaluated before and after intravenous administration of propiverine and specific antagonists for muscarinic receptors (atropine), L-type Ca2+ channels (verapamil), and TRPV1 (capsazepine). Propiverine markedly decreased the amplitude pressure of NVC in SCI rats, which was partially inhibited by atropine. Verapamil also suppressed the amplitude pressure of NVC to the same degree as propiverine. NVC disappeared almost completely after C-fiber desensitization, although capsazepine exerted no evident effects. These findings suggest that muscarinic receptors, L-type Ca2+ channels, and C-fiber afferent nerves contribute to the incidence of detrusor overactivity in SCI, and a drug that has multiple antagonistic effects, such as propiverine, is very effective for the treatment of lower urinary tract dysfunctions in SCI.
Keywords: urogenital pharmacology; drug research; acetylcholine; ca-channels; transient receptor potential channels (TRP)